2020
DOI: 10.3389/fonc.2020.564737
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Automatic Segmentation Model With Dosimetric Metrics for Radiotherapy of Esophageal Cancer

Abstract: Results: Average DSC values were greater than 0.92 except for the spinal cord (0.82), and average MDA values were <0.90 mm except for the heart (1.74 mm). Eleven of the 20 dosimetric metrics of the OARs were not significant (P > 0.05). Although there were significant differences (P < 0.05) for the spinal cord (D2%), left lung (V10, V20, V30, and mean dose), and bilateral lung (V10, V20, V30, and mean dose), their absolute differences were small and acceptable for the clinic. The maximum dosimetric metrics diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…2 and 3). This is in line with results found in other studies for different treatment sites such as head & neck and breast cancer [22,23,26]. To our knowledge, no studies have been published that include multiple types of structure sets, or analyzes both intra-observer variability together with dose difference on a reference contour set.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2 and 3). This is in line with results found in other studies for different treatment sites such as head & neck and breast cancer [22,23,26]. To our knowledge, no studies have been published that include multiple types of structure sets, or analyzes both intra-observer variability together with dose difference on a reference contour set.…”
Section: Discussionsupporting
confidence: 91%
“…Lustberg et al showed significant differences between manual and user-adjusted contours of the heart, mediastinum and esophagus, even though all of them were accepted for clinical use by the same observer [12]. Multiple studies on inter-observer contour variability have been performed for several treatment sites [20][21][22][23][24][25][26]. To the best of our knowledge, no studies have been done that analyzed the influence of autosegmentation methods and intra-/inter-observer variability on the treatment plan outcome for lung cancer.…”
mentioning
confidence: 99%
“…According to the International Commission on Radiation Units and Measurements (ICRU) 83 report, 21 these dosimetric endpoints (D98%, D mean , and D2%) represent the minimum, mean, and maximum doses received by the target. The CI value of target volume is defined according to the following equation, 12 , 21…”
Section: Methodsmentioning
confidence: 99%
“… 9 Recent research has suggested that despite the fact that these geometric indices can be easily calculated, they do not consider the clinical effect and may lack clinical relevance. 10 - 12 Furthermore, different geometric indices have different properties, but different automatic segmentation studies were not based on a uniform guide or rules to select geometric indices to evaluate the contour results. 13 - 15 Subject to the assumption of a reference contour, the method used for the clinical assessment of the accuracy of radiotherapy (RT) contours involves the determination and prediction of the deviation of its dosimetric indices based on the dose distribution of the radiation treatment plan.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ML may also be used to propose risk factors for anastomotic leakage after esophagectomy [120]. Other attempts included using DL to identify optimal dosing of radiotherapy in GEA or defining the optimal target volume and organs at risk [121][122][123][124][125]. A dedicated analysis by Rahman et.…”
Section: Epidemiology Radiation Oncology and Blood Biomarkersmentioning
confidence: 99%